Pengaruh Pelatihan Pegawai, Kepuasan Kerja, Dan Kompensasi Terhadap Kinerja Pegawai Di Rumah Sakit “M” - Aribowo, Antonius Bayu; Djaali, Nur Asniati; Jumhati, Siti (Syntax Literate, 2025)
Employee performance plays an important role in the quality of health services. However, "M" Hospital Surabaya is still facing performance stagnation, patient complaints, and low scores in several work units, so it is necessary to evaluate the factors that affect it so that the service is more optimal. This study aims to analyze the influence of employee training, job satisfaction, and compensation on employee performance at "M" Hospital Surabaya. This study uses a quantitative approach with a cross-sectional design. Data analysis was carried out through univariate, bivariate, and multivariate analysis. The study population was all permanent employees of Hospital "M". The research sample was determined by the Lemeshow formula, obtained a minimum of 132 respondents, then added 30% so that the total was 172 respondents who were taken proportionally from low-performing work units. The results of the study showed that the overall performance of employees was moderate, with the majority of respondents' assessments in the Adequate category. Meanwhile, training and job satisfaction are considered good to very good, and compensation is considered good even though there is still sufficient assessment, thus showing that there is room for improvement, especially in the compensation system and the implementation of factors that support the improvement of employee performance. Multivariate analysis showed a positive and significant relationship between training, job satisfaction, and compensation and employee performance. Of these three factors, compensation is the variable that has the most influence on employee performance at Hospital "M". The management of "M" Hospital is advised to strengthen a competitive compensation system, develop training programs that meet technical and non-technical needs, provide a clear career development path, and build a two-way communication culture to encourage employee performance improvement.